Spatially programmed alignment and actuation in printed liquid crystal elastomers - Rodrigo Telles; Arda Kotikian; Guillaume Freychet; Mikhail Zhernenkov; Patryk Wąsik; Benjamin M. Yavitt; Jorge-Luis Barrera; Caitlyn C. Cook; Ronald Pindak; Emily C. Davidson; Jennifer A. Lewis (Proceedings of the National Academy of Sciences, 2025)
Liquid crystal elastomers (LCEs) exhibit reversible shape morphing behavior when cycled above their nematic-to-isotropic transition temperature. During extrusion-based 3D printing, LCE inks are subjected to coupled shear and extensional flows that can be harnessed to spatially control the alignment of their nematic director along prescribed print paths. Here, we combine experiment and modeling to elucidate the effects of ink composition, nozzle geometry, and printing parameters on director alignment. From rheological measurements, we quantify the dimensionless Weissenberg number ( Wi ) for the flow field each ink experiences as a function of printing conditions and demonstrate that Wi is a strong predictor of LCE alignment. We find that director alignment in LCE filaments printed through a tapered nozzle varies radially when Wi < 1, while it is uniform when Wi ≫ 1. Based on COMSOL simulations and in operando X-ray measurements, we show that LCE inks printed through nozzles with an internal hyperbolic geometry exhibit a more uniform director alignment for a given Wi compared to those through tapered nozzles. Concomitantly, the stiffness along the print direction and actuation strain of printed LCEs increases substantially under such conditions. By varying Wi during printing through adjusting the flow rate “on the fly”, LCE architectures with uniform composition, yet locally encoded shape morphing transitions can be realized.